Assessment of factors influencing job satisfaction among healthcare workers' in public hospitals in Nairobi County, Kenya - Lifuleze CM; Muhonja FH; Muchiri J (Ibom Medical Journal)
Background: According to (Kalinski, 2020) Job satisfaction is a complex combination of psychological, emotional feeling and other environmental factors that can affect an employee positively and give them a sense of achievement on the job. Further, He implys that job satisfaction can be linked to doing a job one enjoys, being productive and getting positive intrinsic rewards like enthusiasm, and contentment. On March 14, 2024 the healthcare worker’s through their union representatves (KMPDU & KNUN) announced a nationwide strike in Kenya. This strike lasted for 56 days and was called off on May 8th 2024 after negotiations, the government officials agreed to some of the union demands. (MoH, 2024). It is evident that Healthcare workers are dissatisfied and the link to the major causes is not clear.